Analysis of Volatile Organic Compounds of Pine Nodular Branch - Wu, Xiaobo; Xue, Jian; Zhang, Linlin (Asian Journal of Chemistry, 2012)
In order to investigate the volatile composition of pine nodular branch, supercritical fluid extraction, steam distillation and solvent extraction was used. The volatile oil was analyzed by gas chromatography-mass spectrometry. In all, 41 volatile components were identified. It was established that the volatile components mainly include some terpenoids compounds, such as pinene, longifolene and caryophyllene. The volatile components of pine nodular branch which was collected from chinese pine (Pinus tabulaeformis Carr.) and masson pin (Pinus massoniana Lamb.) are similar.